Sinergismo antimicrobiano de óleos essenciais e nitrito sobre Clostridium sporogenes inoculado em fiambre de peito de frango - Martins, Heloísa Helena de Abreu (2016)
Clostridium sporogenes are Gram-positive, anaerobic, sporulating, commonly related to food spoilage. Due unto their genetic and physiological similarity to the species of Clostridium botulinum Group I (proteolitical), C. sporogenes is widely used as a substitute for this microorganism in the laboratory. The current consumer demand for natural products has led to research on new antimicrobial agents from plants to improve the safety of food products, so the essential oils of spice stand out because they have antimicrobial activity and most are recognized as safe to health (GRAS). The aim of this study was to determine the minimum bactericidal concentration (CMB) of essential oils of Origanum vulgare, Thymus vulgaris, cubeba Litsea, Myristica fragrans, Ocimum basilicum, aromaticum Syzygium, Piper nigrim and Citrus aurantifolia and combinations thereof and prepare a meat product with reduction of sodium nitrite and adding essential oils, analyzing the growth and sporulation of C. sporogenes, as well as the effect on color, pH, Aw, lipid oxidation and residual nitrite during the product storage time, the temperature under 7 ° and 14 ° C. Four treatments were produced, and treatment 1: 150 ppm nitrite; Tratamento2: 75 ppm nitrite; Treatment3: 75 ppm + essential oils of oregano (0.082%), Litsea (0.082%), nutmeg (0.027%) and clove (0.027%); Treatment4: 75 ppm nitrite + essential oils of basil (0.054%), black pepper (0.054 %%), lemon (0.054%)) and thyme (0.110%). The essential oils showed the lowest CMB, 0.2%, were the oregano, basil and black pepper, while for the Chinese chili oil, clove and thyme CMB was 0.5%. The essential oils of nutmeg and lemon had the highest CMB, which is 1%. Treatment 4 applied to the ham, containing 75 ppm of nitrite + essential oil of basil (0.054%), black pepper (0.054 %%), lemon (0.054%)) and thyme (0.110%) was the most efficient, down of vegetative cells with the storage time for the two temperatures studied. The oils used combinations prevent sporulation. The use of essential oils did not promote representing changes in the objective color of chicken breast ham. There was reduction of pH and increased water activity and lipid oxidation during storage. There was a significant reduction in the amount of residual nitrite during the storage time. The use of essential oils as natural preservatives embedded in cooked meat can be considered a promising alternative for the food industry, since the treatment with essential oils were not different treatments containing only nitrite in most of the physical - chemical analyzes conducted.